PEMBERDAYAAN MASYARAKAT DALAM PENINGKATAN KUALITAS LINGKUNGAN PERMUKIMAN KUMUH DI PROPINSI BALI - Alit, I Ketut (Jurnal Natah; Vol. 3, No. 1 Februari 2005, 2012)
Quality of housing settlement in Bali Province is expressed by local genius of diversity of local community development. The main issue that lead to the change of it, is the factor of population growth both naturally and migration from village to urban. Although many efforts to increase the environment quality of slum settlement, have been conducted by local government, private and community. Yet, many slums area still need to be improved their quality. Those are caused by the lack of finance both provided by government and community. It seems that the community who have strongly local custom and supported by fully together commitment, will be able to increase their quality of housing settlement and environment. Aware of the limited of many sector involved in increasing the environment quality of housing settlement and also realize to the highly local potency of Bali Province, so the approach of community development will be the best option to conduct in order to overcome the growth of slum settlement.
Keywords: environment quality of settlement and community development